Stability of a Class of Impulsive Neutral Stochastic Functional Partial Differential Equations - Yue Liu; Dehao Ruan (Discrete Dynamics in Nature and Society)
In this paper, a class of impulsive neutral stochastic functional partial differential equations driven by Brownian motion and fractional Brownian motion is investigated. Under some suitable assumptions, the pth moment exponential stability is discussed by means of the fixed-point theorem. Our results also improve and generalize some previous studies. Moreover, one example is given to illustrate our main results.